KEPUTUSAN PEMBELIAN BERDASARKAN BAURAN PEMASARAN - Ayu Alfiani Zega; Sylvia Fahzannah; Tio Fanny; Muammar Rinaldi (Niagawan, 2023)
This study aims to determine the effect of price on purchasing decisions on Primebatiq, determine the effect of product quality on purchasing decisions on Primebatiq, determine the effect of price and product quality on purchasing decisions on Primebatiq. The research population that will be used in the study are all Primabatiq users who made purchases during the 2020 period as many as 1,374 consumers. By using the Slovin formula with an error rate of 10%, the number of samples obtained is 93 respondents. The results of the research analysis show that price has a negative and significant effect on purchasing decisions on Primebatiq based on the results of partial hypothesis testing, namely tcount -4.873 < - ttable -1.661. The results of the analysis show that product quality has a positive and significant effect on purchasing decisions on Primebatiq based on the results of partial hypothesis testing, namely tcount 2,258 > ttable 1,661. The results showed that Price and Product Quality had a positive and significant effect on Purchase Decisions at Primebatiq based on the results of simultaneous hypothesis testing, namely Fcount 26.832 > Ftable 2.36. The results of this study are supported by the value of R square (R2)= 0.374 meaning that the Purchase Decision variable can be explained by the Price and Product Quality variable of 37.4% while the remaining 62.6% is influenced by other factors originating from outside this research model such as service, advertising, discount, satisfaction, loyalty, behavior, consumer perception and other variables.